The Effect Of Marination With Red Ginger and Garlic On The Quality Of Beef Jerk - Dedi Saputra, Firman; Nurhaita, Nurhaita; Akbar, Syahro Ali; Sari, Rica Mega; Surtina, Dara; Astuti, Tri (Journal of Animal Nutrition and Production Science, 2024)
The purpose of this study was to determine the effect of marination with red ginger and garlic on the quality of beef jerky by analyzing water content, pH, and total bacterial population. This research used a Completely Randomized Design (CRD) with 4 treatments: P1 (2% fine salt), P2 (3% red ginger + 2% fine salt), P3 (3% garlic + 2% fine salt), and P4 (1.5% red ginger + 1.5% garlic + 2% fine salt), each with 4 replications. The variables measured included water content, dry matter, pH, and total bacterial population. The water content of the jerky ranged from 17.66% to 18.22%, dry matter ranged from 81.75% to 82.28%, and pH ranged from 5.96 to 6.16. Meanwhile, the total bacterial population ranged from 4.73 to 7.16 log CFU/g. The results showed that marination with red ginger and garlic had no significant effect (P>0.05) on water content, dry matter, and pH but had a highly significant effect (P<0.01) on the total bacterial population. The best treatment in this study was P3 (garlic), as it resulted in the lowest bacterial population compared to other treatments.